PERANAN EKOLOGI PEMERINTAHAN DALAM MENINGKATKAN DAYA SAING KEBIJAKAN PEMERINTAH DAERAH - Afriadi Sjahbana Hasibuan (Jurnal Kebijakan Pemerintahan, 2019)
Role of Government Ecology in Increasing Regional Government Policy Competitiveness. Government ecology as a basis for policy making will follow various processes for preparing policy analysis with various resources obtained from both natural resources, artificial resources and human resources. These resources are a reference in the formulation of government policies in building regional competitiveness. This study aims to discuss the role of government ecology in enhancing competitiveness through local government policies to improve services to the public. The method used in this study is library research. Data is collected from a variety of materials in the library such as documents, books, magazines, journals, both offline and online. The results show that local government policies will be more effective when policies are implemented in policy formulation with government-based knowledge or ecology. The Regional Government seeks to have competitiveness that adheres to commitment and is consistent in implementing regional government processes. The process of increasing competitiveness goes hand in hand with increasing knowledge and capabilities of apparatus in public service optimally. Keywords: government ecology, policy, competitiveness.